Performance of Membrane Bioreactor in Removal of Heavy Metals from Industrial Wastewater (Iranian Journal of Chemical Engineering)
Membrane technology is one of the few non-pollutant choices when selecting a treatment process. A membrane with suitable pore size can remove almost all pollutants without using any chemicals. In this research, chromium, zinc and lead were removed from synthetic wastewater by a membrane bioreactor. The results showed that by using a membrane bioreactor, the COD removal efficiency was increased in all conditions in comparison with that of an activated sludge process system. According to the test results, in the case of having heavy metals; Chromium with a concentration below 50 mg/l , the removal efficiency was shown to be about 95% and at these concentrations, chromium has no toxic effect on micro-organisms. However, the Activated Sludge Process showed poor removal efficiency in the case of having zinc. But when ASP was used in conjunction with the membrane, the removal efficiency was increased to 76%. Membrane showed an improvement of efficiency from 44% to 65% in the case of having 50 mg/ l of lead.